Analisis Sistem Penetapan Harga dalam Jual Beli Gambir Ditinjau dari Perspektif Ekonomi Islam di Nagari Muaro Paiti Kecamatan Kapur IX Kabupaten Lima Puluh Kota - Kelvano Arianto; Awaluddin Awaluddin (ARZUSIN, 2026)
The issue of price determination in the gambier commodity trade has received attention in several previous studies; however, studies that specifically examine the compatibility of price-setting mechanisms with Islamic economic principles at the local level remain limited. This study aimed to analyze the price-setting system in gambier buying and selling from the perspective of Islamic economics in Nagari Muaro Paiti, Kapur IX Subdistrict, Lima Puluh Kota Regency. This study used a qualitative approach with a case study design. The research informants consisted of key informants and supporting informants selected through purposive sampling. Data were collected through interviews, observation, and documentation, and were then analyzed using the stages of data reduction, data display, and conclusion drawing. The results showed that gambier price determination was dominated by middlemen by considering demand, market prices, product quality, and the level of competition, whereas farmers tended to be positioned as price takers. Limited access to information and farmers’ dependence on middlemen caused a consistent price gap between the farm-gate level and the market. These findings contribute to the development of price theory studies in Islamic economics, particularly regarding the principles of justice, transparency, and mutual consent in transactions. The conclusion of this study emphasizes the importance of balancing market power and access to information in creating a fairer gambier trading system. The implications of this study indicate the need to strengthen farmer institutions, improve price transparency, and provide policy support for the plantation sector to strengthen farmers’ bargaining position and open opportunities for further studies on strengthening institution- and technology-based commodity trade.